Marine tailings disposal - Ellis, Derek V. (Ann Arbor, Michigan Ann Arbor Science, 1982)
Proceedings of a Symposium on Marine Tailings Disposal held at Ketchikan, Alaska, on March 22-23, 1982"--Pref.Sponsored by U.S. Forest Service, Ketchikan Area et al.
Keywords: Tailings(Metallurgy); Mineral industries; Waste disposal in the ocean